Group Membership Trumps Shared Preference in Five-Year-Olds’ Resource Allocation, Social Preference, and Social Evaluation - Yang, Li; Park, Youjeong (Frontiers in Psychology, 2022)
This study investigated five-year-olds’ priority between shared preference and group membership in resource allocation, social preference, and social evaluation. Using a forced-choice resource allocation task and a friend choice task, we first demonstrate that five-year-old children distribute more resources to and prefer a character who shares a preference with them when compared to a character who has a different preference. Then we pitted the shared preference against group membership to investigate children’s priority. Children prioritized group membership over shared preference, allotting more resources to and showing more preference toward characters in the same group who did not share their preferences than those from a different group who shared their preferences. Lastly, children evaluated resource allocation and social preference in others that prioritized group membership or shared preference. Children regarded prioritization of group membership more positively than prioritization of shared preference from the perspective of a third person. The results suggest that children by five years of age consider group membership as of greater importance than shared preference not only in their own resource allocation and social preference, but also in their evaluation of others’ resource allocation and liking.